IMPACT OF SUBSURFACE DRAINAGE ON SOIL SALINITY IN PAKISTAN - A. H. Azhar (Journal of Animal and Plant Sciences, 2010)
In this study three subsurface drainage projects namely; Fourth Drainage Project, Faisalabad (FDP), Chashma Command Area Development Project (CCADP) and Mirpurkhas Tile Drainage Project (MKDP) have been assessed in terms of their impact on soil salinity improvement in irrigated areas. At FDP, the analysis of surface and profile salinities revealed that both the salinities were significantly decreased. The decrease in surface and profile salinities was 20% and 14% respectively against the benchmark year (i.e. 1984). The surface salinity showed an improvement of 30% in the salt free area. Profile salinity results indicated an improvement of 28% in non saline-non sodic (NS-NS) area. The improvement in S-SN, NS-S and S-S areas was of the order of 50%, 63% & 18% respectively. At CCADP, the salinity of area was very low and was not considered to be a problem in the project area due to drainage system installation. The investigations showed that 17% area was slightly saline, 1% was moderately saline, and 82% area was salt free. At MKDP, profile salinity in bench mark year (i.e. 2000) was 65%. Significant improvement (i.e. 86%) was observed during post-project 2001 year. However, during the year 2002 the profile salinity aggravated and showed improvement of only 14% with respect to bench mark year. Saline-Sodic (S-S) area was reduced by 33% in year 2001. Nevertheless, the situation was reversed showing the deterioration of 11% in year 2002 as compared to bench mark year. The aggravated soil salinity situation during year 2002 was mainly due to the poor operation of drainage system in MKDP area. Overall, the investigations revealed the positive impact of subsurface drainage system installation in terms of salinity control of irrigated lands of affected areas. The rate of improvement was very high in the initial years of systems' operation.
Keywords: impact; subsurface drainage; soil salinity; waterlogging